2020
DOI: 10.3390/ani10081342
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Semi Automated Commercial Closed System for Autologous Leukocyte- and Platelet-Rich Plasma (l-prp) Production in Dogs: A Preliminary Study

Abstract: Background: To characterize the cellular composition (platelets, erythrocytes, and leukocytes) and determine platelet-derived growth factor isoform BB (PDGF-BB) concentration in canine leukocyte- and platelet rich plasma (L-PRP) produced using a commercial semi-automated closed system. Methods: Twenty milliliters of citrated whole blood were obtained from 30 healthy un-sedated canine blood donors and processed using a semi-automated completely closed commercial system (CPUNT 20, Eltek group, Casale Monferrato,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
(163 reference statements)
2
5
0
Order By: Relevance
“…This included much lower PDGF-BB concentrations but at the same time much higher TGF-β1 concentrations in canine concentrates and lysates as compared to the equine counterparts [ 29 ]. These species’ differences in growth factor concentrations and canine growth factor levels widely correspond to the literature, although the results described in different studies are diverse [ 52 , 53 , 54 , 55 ]. In addition, the cPL obtained after lysis showed a significantly lower PDGF-BB concentration in comparison to the canine concentrate.…”
Section: Discussionsupporting
confidence: 74%
“…This included much lower PDGF-BB concentrations but at the same time much higher TGF-β1 concentrations in canine concentrates and lysates as compared to the equine counterparts [ 29 ]. These species’ differences in growth factor concentrations and canine growth factor levels widely correspond to the literature, although the results described in different studies are diverse [ 52 , 53 , 54 , 55 ]. In addition, the cPL obtained after lysis showed a significantly lower PDGF-BB concentration in comparison to the canine concentrate.…”
Section: Discussionsupporting
confidence: 74%
“…This is similar to two of five systems in one study (12) and two of five in another (18). In a study carried out by Perego et al (24) evaluating the CPUNT 20 system, the final product did not have a significantly different leukocyte count compared with whole blood. This system; however, has two settings which gives the user the option of allowing or disallowing leukocytes in the final product.…”
Section: Discussionsupporting
confidence: 78%
“…Only 3 of the 10 subjects demonstrated a final plasma product with a higher concentration of platelets when compared to the initial CBC on peripheral blood (prior to processing). Unlike the system studied here, Perego et al (24) showed that the CPUNT 20 system consistently concentrates canine platelets. However, the Stryker RegenKit PRP system is not the only system of its kind that was shown not to concentrate platelets efficiently.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…At D0, L-PRP was prepared using a semi-automated closed system previously evaluated by the same authors in dogs [ 53 ]. Briefly, the system is composed of a single use, sterile collection kit for blood sampling (CpunT 20 mL, Eltek S.p.A, Hone, AO, Italy), a dedicated centrifuge (Eltek Group, Hone, AO, Italy) and an automatic instrument for the separation of the L-PRP (Eltek Group, Hone, AO, Italy).…”
Section: Methodsmentioning
confidence: 99%